The heterogeneity of the machine tool industry in Brazil - Glaison Augusto Guerrero; Pedro Cezar Dutra Fonseca; Marcelo Arend (EconomiA, 2017)
The current paper aimed to investigate the reasons for the technological and competitive heterogeneity in the machine tool industry in Brazil. By analyzing the trajectory of the sector, we can highlight three main reasons for such heterogeneity. First, due to the competitive framework that emerged from the Brazilian import substitution industrialization process (ISI), the companies that produce and used such technological artifact gave emphasis to the accumulation of productive capacity rather than to innovative capacity. Second, ISI institutional `dynamics' configured the machine tool industry international specialization in products with lower technological content. Third, technological and competitive heterogeneity among manufacturers due not only to different innovative efforts among them, but also to the structure of the demand and the level of sophistication and technological efforts by users. – – O objetivo desse artigo é investigar os motivos da heterogeneidade tecnológica e competitiva do setor de máquinas-ferramenta no Brasil. Através da análise da trajetória do setor, podem-se destacar três raz\~oes principais para tal heterogeneidade. Primeiro, a partir do marco competitivo que emergiu do processo brasileiro de industrializaç\~ao por substituiç\~ao de importaç\~oes (PISI), as empresasprodutoras e usuárias de tal artefato tecnológico deram ênfase para acumulaç\~ao de capacidade produtiva e n\~ao de capacidade inovativa. Segundo, a `dinâmica' institucional do PISI configurou a especializaç\~ao internacional do setor de máquinas-ferramenta em produtos com menor conteúdo tecnológico. Em terceiro, a heterogeneidade tecnológica e competitiva entre os fabricantes decorre n\~ao apenas dos distintos esforços inovativos entre os mesmos, mas também é devida à estrutura da demanda e do grau de sofisticaç\~ao e esforços tecnológicos dos usuários."
Keywords: 330; Machine tools; Brazilian economy; Capital goods; Technology; Máquinas-Ferramenta; Economia Brasileira; Bens de Capital; Tecnologia